The mycoparasite Pythium oligandrum induces legume pathogen resistance and shapes rhizosphere microbiota without impacting mutualistic interactions - Hashemi, Maryam; Amiel, Aurélien; Zouaoui, Mohamed; Adam, Kévin; Clemente, Hélène San; Aguilar, Marielle; Pendaries, Rémi; Couzigou, Jean-Malo; Marti, Guillaume; Gaulin, Elodie; Roy, Sébastien; Rey, Thomas; et al. (Frontiers in Plant Science, 2023)
Pythium oligandrum is a soil-borne oomycete associated with rhizosphere and root tissues. Its ability to enhance plant growth, stimulate plant immunity and parasitize fungal and oomycete preys has led to the development of agricultural biocontrol products. Meanwhile, the effect of P. oligandrum on mutualistic interactions and more generally on root microbial communities has not been investigated.Here, we studied the effect of P. oligandrum on Medicago truncatula and Pisum sativum, two legume plants. We found that P. oligandrum promotes plant growth in these two species and protects them against infection by the oomycete Aphanomyces euteiches, a devastating legume root pathogen. In addition, we documented by RNA-sequencing how P. oligandrum up-regulated more than 1000 genes in M. truncatula roots including genes involved in plant defense and notably in the biosynthesis of antimicrobial compounds and validated the enhanced production of M. truncatula phytoalexins, medicarpin and formononetin by metabolomics fingerprinting. Despite this activation of plant immunity, we found that root colonization by P. oligandrum did not impaired symbiotic interactions, promoting the formation of large and multilobed symbiotic nodules with Ensifer meliloti and did not negatively affect the formation of arbuscular mycorrhizal symbiosis. Finally, metagenomic analyses showed the oomycete modifies the composition of fungal and bacterial communities. Together, our results provide novel insights regarding the involvement of P. oligandrum in the functioning of plant root microbiota.